VIRAL ANTIBODIES IN PRESCHOOL CHILDREN - S. Saidi (Tehran University of Medical Sciences, 1974)
One hundred sera from children 1 - 6 years of age, representative of a large serum collection, were tested for the prevalence of antibodies against different viruses. Hemagglutination-inhibition (HI) antibodies were found in 68% for measles; 61 % for rubella; 75'% for influenza A2/Hong Kong/68, 16% for influenza B/Md./59, 0% for group A arboviruses, 10% for group B arboviruses, 3% for phlebotomus fever group and 4% for Congo-Crimean hemorrhagic fever (C-CHF) group of arboviruses Poliomyelitis-neutralizing antibodies for type 1, 2 and 3 were 90%; 85% and 84%~ respectively. Antibody to EH virus was detected in 84% of the sera by immuno-fluorescence. None of the sera were positive for hepatitis-B antigen or antibody by immuno-precipitation test. The prevalence of some viral antibodies found in this survey are compared with results obtained from surveys in other parts of the country.